CHURCH LAW AND BANTU MUSIC, by Stephen B. G. Mbunga, approx. 16 x 24 cms., 216 pp. plus XXXI; 1963. 22 Swiss francs (37 sh. or $5.10): Nouvelle Revue de Science Missionnaire, Schoneck-Beckenried, Switzerland (for Southern Africa, payable at P.O. Box 622, Gwelo, S.R.) - Basil, Brother (International Library of African Music, 1963)
pages: 55-56
Keywords: African Music